2004
DOI: 10.1007/bf02482176
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological examination of glioma by proton magnetic resonance spectroscopy background

Abstract: Automation of proton magnetic resonance spectroscopy (MRS) in recent years has made it possible for MRS measurement to be performed in a shorter time than before, and the number of reports of its usefulness for the assessment of glioma malignancy has been increasing in the past several years. We studied the efficacy of proton MRS when used for glioma and conducted clinicopathological examination of glioma. The subjects were 15 patients who had received a pathological diagnosis of glioma at our hospital (6 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
1
3
0
1
Order By: Relevance
“…In our experiences, the MRS data can provide unique information that when combined with BOLD and DTI has implications for defining tumor type and grade, directing biopsy or surgical resection. To review the findings of this study and relative literatures (1,3,4,(6)(7)(8)(15)(16)(17)(18)19,28,31,38), typical changes of various metabolites among different types of lesions were summarized in Table II. The value of proton MRS for predicting tumor malignancy which was known as an important branch of clinical application has been reported in several prior clinical studies (5,(12)(13)(14)19,22,27). Similar to our results, the ratio of Cho/Cr and Cho/NAA in high grade gliomas were found significantly higher than in low grade gliomas, and lipid peak was usually defined in high grade gliomas, which was strongly associated with the presence and amount of necrosis in glioma.…”
Section: Shang H Et Al: Preoperative Assessment Of Glioma Using F-mrisupporting
confidence: 91%
“…In our experiences, the MRS data can provide unique information that when combined with BOLD and DTI has implications for defining tumor type and grade, directing biopsy or surgical resection. To review the findings of this study and relative literatures (1,3,4,(6)(7)(8)(15)(16)(17)(18)19,28,31,38), typical changes of various metabolites among different types of lesions were summarized in Table II. The value of proton MRS for predicting tumor malignancy which was known as an important branch of clinical application has been reported in several prior clinical studies (5,(12)(13)(14)19,22,27). Similar to our results, the ratio of Cho/Cr and Cho/NAA in high grade gliomas were found significantly higher than in low grade gliomas, and lipid peak was usually defined in high grade gliomas, which was strongly associated with the presence and amount of necrosis in glioma.…”
Section: Shang H Et Al: Preoperative Assessment Of Glioma Using F-mrisupporting
confidence: 91%
“…According to Izumiyama et al ( 2004), glioma malignancy is likely to increase when NAA levels decrease. In the current study, declines in NAA in all gliomas demonstrated that the neurons had been invaded and substituted for neoplasia, resulting in a significant reduction in the number of neurons and a drop in signal intensity [29]. According to Liu et al (2012), none of the diagnosed lowgrade gliomas had a lipid peak, whereas most high-grade gliomas, particularly glioblastoma multiformis, had higher lipid peaks [30].…”
Section: Discussionmentioning
confidence: 43%
“…Investigators have already used magnetically labeled cells in a different clinical setting to target the migration of dendritic cells, neural stem cells, bone marrow derived CD34+ cells and islet grafts [41][44]. Despite the advancement in imaging modalities, the early detection of residual tumor or metastatic foci in glioblastoma multiforme patients is still controversial, especially in the areas with a mixture of inflammation and malignancy [9], [10], [45], [46]. Since magnetic labeling of cells does not interfere with radionuclide or PET tracer accumulation in genetically engineered cells [47], it will be possible to combine these two approaches to clinically monitor and functionally assess the temporal and spatial migration of cells using the recently introduced PET/MRI systems [48].…”
Section: Discussionmentioning
confidence: 99%